Anxiety and enjoyment in L2 video-mediated interactions with native speakers: An idiodynamic approach - Guo, Xinyue; Wang, Man (Studies in Second Language Learning and Teaching, 2026)
Anxiety and enjoyment, a contrastive pair of emotions that significantly affect second language (L2) learning, have been widely investigated under the framework of complex dynamic systems theory. With the growing popularity of video-mediated interactions (VMIs), the investigation of anxiety and enjoyment in online settings is important but underexplored. This study examines the relationship between anxiety and enjoyment in L2 VMIs, using an idiodynamic approach. Four L2 learners completed video-mediated conversations with native speakers (NSs) in English via an online platform and rated their anxiety and enjoyment separately while reviewing their video recordings. Subsequent interviews were carried out to explore the categories of factors influencing these emotions. The findings revealed that the relationship between anxiety and enjoyment was more than a seesaw pattern, with these two emotions converging and diverging at specific events. Moreover, we found that anxiety and enjoyment were influenced by three categories of factors: individual, interpersonal, and environmental. The triangulation of emotion ratings, stimulated recall interview data, and performance data helped build a richer understanding of emotions in L2 speaking within the VMI context and yielded practical pedagogical implications for enhancing L2 learners’ emotional experiences during L2 oral interactions.